The National Element in Hermann Cohen's Philosophy and Religion - Wiedebach, Hartwig (Supplements to The journal of Jewish thought and philosophy., 2012)
Hermann Cohen was a Jewish-German thinker with a passion for philosophy. Two forms of national engagement influenced his philosophical system and his Jewish thought: a cultural-political 'Germanness' (Deutschtum) and a religious Judaism beyond the political.